The Role of Bifidobacterium SPP. on Cholestrol Assimilation in the in Vitro and in Vivo Studies - Sabet, Maryam Rezaei (2001)
The purpose of this study was to investigate the cholesterol removal by some bifidobacterium spp. at in vitro and in vivo conditions with the emphasis of their bile salt deconjugation ability. Bile salt hydrolase (BSH) activity, which is the measurement of enzyme activity responsible for bile salt deconjugation, was quantified by high pressure liquid chromatography (HPLC) assay. B. in/antis G001204 was the isolate with the highest deconjugation rate in TPY broth supplemented with 5mM GCDC. Generally all the isolates deconjugated glycoconjugated bile acid in higher amount (P<0.05) compared to tauroconjugates. Likewise in overall the percentage of deconjugation activity was higher in TPY medium supplemented with 5mM bile acids (P<0.05) compared to the TPY broth with 10mM bile acids. Cholesterol removal from media was strain-dependent. The percentage of cholesterol assimilated in TPY containing 0.52mM cholesterol plus bile acids ranged from 4.0% for B. infantis F41134 to 47.0% for B. infantis G001204. The presence of bile salt was prerequisite for cholesterol removal.Results of the in vivo experiment showed that total cholesterol concentration in rats fed on the high-cholesterol diet plus either B. in/antis 0001204 or B. animalis ATCC 27672 in a 2-week period were significantly (P<0.05) lower than the control group. Total fecal bile acid excretion increased in animal groups throughout the high-cholesterol diet feeding and probiotic-treated groups had higher excretion rate of fecal bile acids compared to the control significantly (P<0.05).